Naturaleza, sociedad y conflictividad socio-ambiental. Una mirada desde la justicia restaurativa (Papeles, 2021)
Over the last few decades, the linkages of the Latin American economies with the globalised internationaleconomy, centered on the primarisation of the economies, has fostered a development model based on the pillaging of natural assets and the dispossession of indigenous and peasants’ land. Against this backdrop, grave human rights violations and severe damages to ecosystems have been perpetrated, whilecorporations have been widely benefited, with the complicity of the states. Consequently, the number of socio-environmental conflicts has escalated, due to an unjust distribution of ecological resources. This paper explores socio-environmental conflicts in Argentina as windows into crucial conversations about thecurrent global crisis, through the lenses of restorative justice.